(untitled) (Bangladesh Journal of Medical Science, 2017)
Introduction: Aim of this study was to evaluate the effective of premedication and to determine the difference between non steroidal anti- inflammatory drugs and centrally acting opioids like tramadol on success rate of inferior alveolar nerve block in patients with asymptomatic irreversible pulpitis. Methods: This double blind clinical study was conducted on 60 patients with asymptomatic irreversible pulpitis in first or second mandibular molar with normal periapical radiographic findings. Three medications i.e., ibuprofen (600mg), tramadol (50 mg) and combination of ibuprofen (400 mg) + acetaminophen (325) were compared and lactose powder capsules were taken as placebo. All patients received IANB and teeth were examined with a cold pulp test using endofrost. Then, endodontic access cavity preparation was initiated. In case of pain during treatment, patients were asked to rate their pain on the visual analog scale. Results: The tramadol group showed significantly higher success rates but ibuprofen and combination of ibuprofen and acetaminophen groups were not significant with placebo (p>05). No Significant differences were there regarding sex of the patients. Conclusion: Premedication with tramadol increased the success rate of IANB. Bangladesh Journal of Medical Science Vol.16(3) 2017 p.370-374